Characterization of the mechanisms by which missense mutations in the lysosomal acid lipase gene disrupt enzymatic activity. (27th May 2019) - Vinje, Terje; Laerdahl, Jon K; Bjune, Katrine; Leren, Trond P; Strøm, Thea Bismo
Abstract: Hydrolysis of cholesteryl esters and triglycerides in the lysosome is performed by lysosomal acid lipase (LAL). In this study we have investigated how 23 previously identified missense mutations in the LAL gene ( LIPA ) (OMIM# 613497) affect the structure of the protein and thereby disrupt LAL activity. Moreover, we have performed transfection studies to study intracellular transport of the 23 mutants. Our main finding was that most pathogenic mutations result in defective enzyme activity by affecting the normal folding of LAL. Whereas, most of the mutations leading to reduced stability of the cap domain did not alter intracellular transport, nearly all mutations that affect the stability of the core domain gave rise to a protein that was not efficiently transported from the endoplasmic reticulum (ER) to the Golgi apparatus. As a consequence, ER stress was generated that is assumed to result in ER-associated degradation of the mutant proteins. The two LAL mutants Q85K and S289C were selected to study whether secretion-defective mutants could be rescued from ER-associated degradation by the use of chemical chaperones. Of the five chemical chaperones tested, only the proteasomal inhibitor MG132 markedly increased the amount of mutant LAL secreted. However, essentially no increased enzymatic activity was observed in the media. These data indicate that the use of chemical chaperones to promote the exit of folding-defective LAL mutants from the ER, may not have a great therapeutic potential as long as these mutants appear to remain enzymatically inactive.